Toxic Systemic Reaction after Bee Stings in a Bitch - Silva, Françoise Louanne Araújo; Botelho, Ana Flávia Machado; Wagatsuma, Mariane Martins; e Paiva, Heloisa Penedo; Bicalho, Ana Leticia Ferreira; Melo, Marília Martins (Acta Scientiae Veterinariae, 2022)
Background: Bee sting poisonings are common in dogs, and toxic systemic presentation may represent a life-threatening condition. Apis mellifera venom is a complex mixture of melitin, apamine, phospholipase, hyaluronidase and degranulating peptides, that causes local injury at the site of inoculation and multiple organ complications, including hemolysis, kidney injury, muscular damage, cardiovascular and respiratory complications. The present work reports a complete and detailed description of a dog’s systemic toxic reaction to bee stings, including history, clinical signs, laboratory findings, emergency care and development, as well as possible association with later immunomediated arthritis. Case: A 6-year-old female German Shepperd suffered multiple bee stings. First care was conducted by a veterinary at the site, where he only received promethazine, meloxicam and dexamethasone. After 24 h and significant progression of symptoms, the animal was forwarded to a specialized veterinary hospital. The patient was evaluated throughout 9 days, and presented intense edema, respiratory distress, tongue necrosis and grade II of acute kidney injury. Extensive laboratory exams were conducted throughout the hospitalization. Main laboratory findings included polycythemia, leukocytosis by neutrophilia and monocytosis, thrombocytopenia and azotemia. Urinalysis evidenced turbid aspect, dark yellow color and intense proteinuria, reinforcing kidney damage. Abdominal ultrasound examination identified blood clots in the bladder, and liver with reduced echogenicity and echotexture, suggesting acute inflammation. Therapy aimed to stabilize the patient, control kidney damage and avoid anaphylaxis. Treatment included intensive care support, promethazine, hydrocortisone, dexamethasone, dipyrone, methadone, metronidazole, ampicillin, clindamycin and tramadol. Following successful treatment, the animal presented immunomediated polyarthritis, possibly associated to both the poisoning and later diagnosed hemoparasitosis (both Erlichia and Babesia). Discussion: Massive bee attacks can cause severe complications, however, data regarding emergency care records are scarce. Based on clinical signs and laboratory findings, the patient presented toxic systemic reaction, including grade II of acute kidney injury and significant cardiorespiratory distress. Another important complication was tongue necrosis, that demanded attention and special supportive care, including feeding tube and specific feed. Treatment also focused in reducing edema and control possible anaphylaxis, providing analgesia and antibiotic therapy. Laboratory findings have been previously described, with evidence of immune-mediated reaction. Follow-up consultations revealed normal parameters, and an unusual presentation of claudication. Investigation concluded that polyarthritis could be responsible for such finding and may be a result of the deposition of immunomediated complexes in the joints, due in this case to the bee poisoning and later positive diagnosis for both Erlichia and Babesia. Systemic reactions to bee stings are complex, and full clinical and laboratory profile aid in both the prognosis and treatment options. Special attention must be given to tongue damage and supportive care is essential for maintaining feeding conditions. Arthritis should be considered as possible complication, reinforcing the importance of follow-up consultations. Keywords: bee attack, dog, envenomation, melittin; poisoning, phospholipase A2.